We learned we can do something to reduce bullying: Children designing anti-bullying mobile apps to empower their peers - Hartikainen, Heidi; Ventä-Olkkonen, Leena; Iivari, Netta; Sharma, Sumita; Lehto, Essi; Molin-Juustila, Tonja; Holappa, Jenni (Frontiers in Education, 2023)
Mobile applications have thoroughly pervaded the lives of children of today, who live and learn through and with such apps. However, limited research has been conducted on children designing such apps and not only using those designed by adults. Inviting children to design such apps is the focus of our study. Moreover, in contemporary society it is emphasized that children are to be empowered to take civic action and engage in making the world a better place. In the literature, however, less focus has been put on how children can be invited to do so by the means of digital technology, particularly mobile application design. In this study, 13-15 years old children are invited to take civic action to tackle the serious societal problem of bullying through the design of mobile apps. We discuss the design process and analyze the applications children designed from the viewpoint of how they aim at tackling bullying. We examine how their app designs aim at empowering other children in the context of bullying and hence consider what kind of opportunities emerge for children to learn skills relating to prevention or management of bullying in the app designs by children. We show that the children’s app designs inform us of the seriousness of the problem of bullying in children’s lives and that they advocate empowerment of other children in different senses. Hence, we increase the understanding of how smart, interactive technologies designed by children address learning and empowerment of other children, i.e., the users of the applications. We also study the learning of the children involved from their own and from their teachers’ perspective. The study showcases an alternative way how educators can integrate digital technologies and apps in school settings to educate children on important societal matters and on digital technology.